FEMINISM: AN OVERVIEW (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2023)
It is seen that there have been discussion in broad way on the women centred issues in our society today. The relevancy of such discussion, of course, can’t be denied if we look to the present position of women's status in our society right from the traditional phase. Rather we must say that the discussion should be more brood based for making women rights effective today. For any fruitful result that sort of discussion of course should be carried out in a impartial and well thinking manner so that the society can fully realise the issue and move with proper direction for its solution without any contradiction to its counterpart. But, so far our knowledge is concerned, we have not seen any possibility due to some defects within itself, which can’t be considered as good sign and may be more harmful for healthy living of women instead of heaving a dignified life. In this essay, we have therefore made an attempt to highlights some major dimensions of women centric issues and problems on the lights of feminist movement today.